Electrochemical determination with a long-length carbon nanotube electrode of quercetin glucosides in onion, apple peel, and tartary buckwheat. (1st December 2019) - Takahashi, Shota; Muguruma, Hitoshi; Osakabe, Naomi; Inoue, Hitoshi; Ohsawa, Tatsuya
Highlights: Individual quercetin glucosides in food are quantified by electrochemical method. This method does not involve a separation and an external standard addition. A long-length carbon nanotube electrode has attractive properties for this purpose. Accurate data in onion, apple peel, and tartary buckwheat are obtained. Abstract: Since the intake of quercetin glucosides has healthy benefits, the analysis of quercetin glucosides in food is useful. The electrochemical determination of individual quercetin glucosides (quercetin-3-glucoside (Q3G), quercetin-4′-glucoside (Q4′G), and quercetin-3, 4′-diglucoside (Q34′G)) in food is carried out. For the detection of quercetin glucosides, a long-length carbon nanotube electrode offers attractive properties such as well-defined current peaks, high sensitivity, and high reproducibility. Cyclic voltammetry (CV) demonstrates distinct and specific peak currents: the oxidation peaks at +0.37, +0.45, and +0.78 V are assigned to the catechol group in the B-ring of Q3G, the 3-hydroxy group in the C-ring of Q4′G, and the resorcinol group in the A-ring of both Q4′G and Q34′G, respectively. Currents, which are determined by CV, of individual quercetin glucosides at the peak potential are proportional to the concentrations of onion, apple peel, and tartary buckwheat, which show good agreement with those obtained by high-performance liquid chromatography.